Diagnosing Memory Provisioning in IaaS Clouds - Pfitscher, Ricardo J.; Pillon, Mauricio A.; Obelheiro, Rafael R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
Infrastructure-as-a-service (IaaS) clouds enable customers to allocate computing resources in a flexible manner to satisfy their needs, and pay only for the allocated resources. One of the challenges for IaaS customers is the correct provisioning of their resources. Many users end up under provisioning, hurting application performance, or over provisioning, paying for resources that are not really necessary. Memory is an essential resource for any computing system, and is frequently a performance-limiting factor in cloud environments. Our work uses monitoring to enable a cloud customer to determine if the memory allocated to his virtual machines is correctly provisioned, under provisioned, or over provisioned. Experimental results with the Xen platform demonstrate the effectiveness of the proposed approach.